Sleep apnoea: clinical importance and facilities for investigation and treatment in the UK. Addendum to the 1993 Royal College of Physicians Sleep Apnoea report. - Gibson, G; Douglas, N; Stradling, JR; London, DR; Semple, S (1998)
The potential importance of the obstructive sleep apnoea syndrome (OSA) has been recognized only in the last few years. Epidemiological studies suggest that symptomatic OSA occurs in 1-2% of middle-aged men and in approximately half that number of women. The relation of OSA to vascular disease is uncertain and the main indication for treatment is the relief of disabling sleepiness. Two recent evidence based analyses have produced diametrically opposed conclusions on the efficacy of treatment with nasal continuous positive airway pressure (CPAP). However, recent controlled studies confirm the overwhelming clinical experience of benefit. Facilities for the investigation and treatment of patients with OSA in the UK are subject to severe financial constraints and the availability of CPAP treatment lags markedly behind that in other countries for which data are available.